Hubungan Antara Resiliensi dengan Kualitas Kehidupan Kerja pada Karyawan di PT. Suriatama Mahkota Kencana Cabang Suzuya Katamso - H. C. Della Nadhiya; Jiang Nara; Friyanka H. D. Sitorus; Josua Valentino; Mukhaira El Akmal (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Quality of work life is one of the important factors that influence employee well-being and performance in an organization. One factor suspected of playing a role in improving the quality of work life is resilience, namely the ability of individuals to adapt and recover from various pressures and challenges in the work environment. This study aims to analyze the relationship between resilience and quality of work life among employees of PT. Suriatama Mahkota Kencana, Suzuya Katamso Branch. The study used a quantitative approach with a correlational design. Data were collected by distributing resilience scales and quality of work life scales to employees, then analyzed using Pearson Product Moment correlation. The results showed a positive and significant relationship between resilience and quality of work life with a correlation coefficient of r = 0.810 and a significance value of p = 0.000 (p < 0.05). This finding indicates that the higher the level of employee resilience, the higher the perceived quality of work life. The coefficient of determination analysis showed that resilience contributed 65.7% to the variation in quality of work life, while 34.3% was influenced by other factors not examined. This study emphasizes the importance of developing resilience as an effort to improve the quality of employee work life